Perancangan dan Pembuatan Orthosis Flat Foot dengan Metode Reverse Engineering dan Rapid Prototyping - Putera, Finny Pratama; Puspaputra, Paryana; Sabdahu, Damarjati (Faculty of Industrial Technology Universitas Islam Indonesia, 2025)
An orthosis is a special device designed to support or improve body structure. In the case of flat feet, an orthosis helps support the arch, provide pressure damping, and increase stability, thereby reducing pain and discomfort. Flat foot is a foot deformity characterized by a lack of arch in the arch. A flat-foot orthotic insole is needed as one of the treatment therapies. The insole design is created using Reverse Engineering and Rapid Prototyping methods and is made according to the specified design criteria. This flatfoot insole is custom-fitted to the patient's anatomical size and printed in Thermoplastic Polyurethane (TPU) on a 3D printer. The result is a shoe insole that is flexible in design and practical in manufacturing.